2009
DOI: 10.1158/1078-0432.ccr-08-3159
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Replicative and Stress-Induced Senescence by RSK4, which is Down-regulated in Human Tumors

Abstract: Purpose: The control of senescence and its biochemical pathways is a crucial factor for understanding cell transformation. In a large RNA interference screen, the RSK4 gene was found to be related to p53-dependent arrest. The purpose of the present study was to investigate the potential role of RSK4 as a tumor suppressor gene. Experimental Design: RSK4 expression was determined by quantitative real-time PCR and immunoblot in 30 colon and 20 renal carcinomas, and in 7 colon adenomas. Two HCT116 colon carcinoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…Very few studies have reported increased tumor-derived RSK expression. Rather, accumulating evidence support the idea that at least some RSK isoforms are downregulated in certain cancers (in particular RSK3 and RSK4 [44, 45]). While our data indicate a requirement for RSK1 and RSK2 (with RSK2 playing a more important role) in Ser1134 and Ser1161 phosphorylation of SOS1 in response to growth factor stimulation, further investigation will be necessary to determine the extent RSK3 or RSK4 participate in the regulation of SOS1 in other cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have reported increased tumor-derived RSK expression. Rather, accumulating evidence support the idea that at least some RSK isoforms are downregulated in certain cancers (in particular RSK3 and RSK4 [44, 45]). While our data indicate a requirement for RSK1 and RSK2 (with RSK2 playing a more important role) in Ser1134 and Ser1161 phosphorylation of SOS1 in response to growth factor stimulation, further investigation will be necessary to determine the extent RSK3 or RSK4 participate in the regulation of SOS1 in other cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…RSKs are directly regulated by ERK signaling and are implicated in cell growth, survival, motility, and senescence (25)(26)(27)(28). Here, we present evidence that overexpression of RSK3 and RSK4 supports cellular proliferation under PI3K pathway blockade by inhibiting apoptosis and regulating cellular translation through phosphorylation of ribosomal proteins S6 and eIF4B.…”
Section: Introductionmentioning
confidence: 68%
“…RSK4 is an outlier and functionally distinct, showing low expression compared with other RSKs, and overexpression of RSK4 may restrict cell growth (12). Several studies have reported that high expression of RSK4 in breast cancer cells is anti-oncogenic, anti-invasive, and anti-metastatic (13), and RSK4 also exhibits a tumor suppressor effect in colon and renal carcinomas (14).…”
Section: Introductionmentioning
confidence: 99%